If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = 18 + 2x Reorder the terms: -2 + 6x = 18 + 2x Solving -2 + 6x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 6x + -2x = 18 + 2x + -2x Combine like terms: 6x + -2x = 4x -2 + 4x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 4x = 18 + 0 -2 + 4x = 18 Add '2' to each side of the equation. -2 + 2 + 4x = 18 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 18 + 2 4x = 18 + 2 Combine like terms: 18 + 2 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| -3(7-4)=-4 | | X+y+9z=-8 | | -1x+-2=1+-2x | | 8x+63=x-21 | | X+6=7.7 | | (-1/3)t=4/3 | | 4/7x-8=-12 | | 19x-6=13x+9 | | 2(3x-3)-4(5x-3)=x(x-3)-x(x+5) | | 3x+2=6x-28 | | (-1/3t=4/3 | | -7(y+2)+3(4y-4)=4(y-3)+8 | | X-61=15 | | A^2=5a+104 | | F(x)=-3x^3-15x^2-12x | | x/-15=-6 | | -36=4w-8 | | 11-2(p+5)=p-5 | | 7x^2+45x+50=0 | | 2(3x-3)-4(5x+3)=x(x-3)-x(x+5) | | 8x-5-11x=9+4x | | 18=(-1/2)y | | 10/1×5/6 | | 3x-11=-23 | | 9(x-1)=9x+11 | | (3x)*(3x)-1=(3x-1)(2x+5) | | 6(y-6)-(y+2)=2 | | V^2-2v+45=5-18v | | F(x)=x^4-8x^2+16 | | -7=u-8 | | 3c-9d+7d+5d= | | 30+3h=6h |